Experimental research on silicon carbide photoconductive semiconductor switch. Issue 8 (August 2015) - Sun, Yanling; Yang, Meng; Song, Chaoyang; Guo, Hui; Jiang, Shuqing
ABSTRACT: Silicon carbide photoconductive semiconductor switches with the good performance of breakdown voltage above 10 kV and ∼16‐Ω minimum on‐resistance are fabricated and tested. A good electrical pulse output is obtained when the switch is triggered by optical pulses. The output performances with different bias voltages are discussed, and the results indicate that the nonlinear output will not occur with the bias voltage increasing. The effects of bias voltage and optical pulse energy on the on‐resistance are investigated. The performance of different switch samples is compared. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1946–1948, 2015